Fibrinogen and tumors - Wu, Xinyuan; Yu, Xiaomin; Chen, Cheng; Chen, Chenlu; Wang, Yuxin; Su, Dongyan; Zhu, Liqing (Frontiers in Oncology, 2024)
Elevated plasma fibrinogen (Fg) levels consistently correlate with an unfavorable prognosis in various tumor patient cohorts. Within the tumor microenvironment, aberrant deposition and expression of Fg have been consistently observed, interacting with multiple cellular receptors and thereby accentuating its role as a regulator of inflammatory processes. Specifically, Fg serves to stimulate and recruit immune cells and pro-inflammatory cytokines, thereby contributing to the promotion of tumor progression. Additionally, Fg and its fragments exhibit dichotomous effects on tumor angiogenesis. Notably, Fg also facilitates tumor migration through both platelet-dependent and platelet-independent mechanisms. Recent studies have illuminated several tumor-related signaling pathways influenced by Fg. This review provides a comprehensive summary of the intricate involvement of Fg in tumor biology, elucidating its multifaceted role and the underlying mechanisms.